(untitled) (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Bacterial resistance has reached an alarming proportion in developing countries because of various reasons like indiscriminate use of antibiotics and its availability as over the counter (OTC) drugs. This study is to get an overview of students understanding of antibiotics and to compare the knowledge, attitude and practice (KAP) on antibiotic use among undergraduate medical students. Material and methods: This was a descriptive cross-sectional study conducted among undergraduate medical students of Janaki Medical College. A structured and customized self-administered questionnaire was used to collect data on socio-demographic and knowledge, attitude and practice (KAP) regarding antibiotic use of medical students. Data were analyzed using SPSS version 20. P < 0.05 was considered statistically significant. Results: Out of 183 undergraduate medical students from first, second and third year of Janaki medical College, 115 (62.8%) were male and 68 (37.2%) were female. Among medical students, mean rank of knowledge on antibiotic use among first year (mean rank = 89.36) and second year (mean rank = 87.50) was lower compared to third year (mean rank = 97.78). The mean rank for attitude among first year (mean rank = 87.75) and second year (mean rank = 94.38) was lower compared to third year (mean rank = 94.56). Likewise, practice of antibiotic use was low among first year (mean rank = 61.27) and second year (mean rank = 105.91) compared to third year students (mean rank = 115.19). There is significant difference of mean rank for the practice (p<0.0001) but not for knowledge and attitude on antibiotic use among the students studying in different years. Conclusion: This study showed varying level of knowledge, attitude and practice on antibiotics use among undergraduate medical students of first, second and third year, suggesting that continuous educational intervention on rational use of antibiotic should be made mandatory in the all the academic years of undergraduate medical curriculum, for promoting judicious use of antibiotics, minimizing self-medication and impacts of antibiotic resistance, and for rational antibiotics prescription by future doctors.